2012
DOI: 10.1299/jtst.7.288
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Condensation/Evaporation and Velocity Distribution of N-Dodecane at Liquid-Vapour Phase Equilibria

Abstract: Some recent results of molecular dynamics simulations of the condensation/evaporation and velocity distribution of n-dodecane (C 12 H 26 ), the closest approximation to Diesel fuel, at a liquid-vapour interface in equilibrium state are briefly described. It is shown that molecules at the liquid surface need to gain relatively large translational energy to evaporate. Vapour molecules with large translational energy can easily penetrate deep into the transition layer and condense in the liquid phase. The evapora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Forf z+ ref , the results for velocity distribution functions obtained by other measurement methods showed a similar tendency, as shown in Refs. [11,18]. Furthermore, before and after the reflection of the molecules, we found that the velocity distribution functions in the z direction almost coincide with each other.…”
Section: Reflecting Molecules At the Vapor Boundarysupporting
confidence: 55%
See 4 more Smart Citations
“…Forf z+ ref , the results for velocity distribution functions obtained by other measurement methods showed a similar tendency, as shown in Refs. [11,18]. Furthermore, before and after the reflection of the molecules, we found that the velocity distribution functions in the z direction almost coincide with each other.…”
Section: Reflecting Molecules At the Vapor Boundarysupporting
confidence: 55%
“…Moreover, the velocity distribution functions of the evaporating and condensing molecules were almost the same as the Maxwell distribution at a liquid temperature of 85 K. However, the temperatures of the velocity distribution functions were slightly higher than that of the Maxwell distribution: a temperature of approximately 89.5 K was obtained from the nonlinear least square method, which leads to the increase of average velocity of evaporating or condensing molecules. According to the recent studies [16][17][18], when molecules evaporate or condense at the interface, the translational energy of the molecules becomes higher than that of molecules in the bulk phase. Also, the increasing of the temperature obtained from the velocity distribution function of evaporating molecules was reported [11,18], which agrees with the present results.…”
Section: Evaporating and Condensing Molecules At The Vapor Boundarymentioning
confidence: 99%
See 3 more Smart Citations